Dietetics Program Directors in the United States Support Teaching Vegetarian and Vegan Nutrition and Half Connect Vegetarian and Vegan Diets to Environmental Impact - Hawkins, Irana W.; Mangels, A. Reed; Goldman, Robert; Wood, Richard J. (Frontiers in Nutrition, 2019)
Registered Dietitian Nutritionists (RDNs) are clinicians trained in the application of food, nutrition, and dietetics. Vegetarians and vegans have a lower risk of many nutrition-related chronic diseases that are epidemic while vegetarian and vegan diets are associated with reduced environmental impact. Despite this strong diet-disease and diet-environment connection, it is not known if dietetics students are taught the principles of vegetarian and vegan nutrition. The objectiveoverarching goals of our study was to investigate curricular practices in accredited dietetics training programs in the United States (U.S.) including 1) the prevalence and perceived importance of vegetarian and vegan nutrition instruction and 2) if program directors connect vegetarian and vegan diets to climate change mitigation and resource conservation. Primary data were collected by way of a cross-sectional, Internet-based survey. All Accreditation Council for Education in Nutrition and Dietetics (ACEND) program directors in the U.S. (N=574) were sent a 37-question survey and invited to participate in the study (N=574).. Outcome measures included the prevalence of vegetarian and vegan nutrition instruction, quantifying if relationships exist among variables, and the frequency of connecting vegetarian and vegan diets to environmental impact. Descriptive and inferential statistics were utilized. Respondents (n=205) indicated that over 51% of programs teach vegetarian nutrition while 49% teach vegan nutrition. There were significant differences between program type and the prevalence of vegetarian (p=0.00005) and vegan (p=0.00005) nutrition instruction. Over 90% of program directors believe that vegetarian and vegan nutrition should be taught. Over 50% of programs identify the connection between vegetarian and vegan diets in climate change mitigation and resource conservation. Most ACEND program directors believe vegetarian and vegan nutrition should be taught. and half connect diet to environmental concern. Nevertheless, there is a discrepancy between beliefs and practice behaviors. These results suggest the need for increased collaboration and the use of novel techniques that better incorporate vegan and vegetarian nutrition throughout dietetics education.